Links Between Adiponectin and Dementia: From Risk Factors to Pathophysiology - Chen, RuiJuan; Shu, Yi; Zeng, Yi (Frontiers in Aging Neuroscience, 2020)
With the aging population, dementia is becoming one of the most serious and troublesome global public health issues. Numerous studies have been seeking effective strategies to delay or block its procession, but with little success. In recent years, adiponectin as one of the most abundant and multifunctional adipocytokines related to anti-inflammation, regulating glycogen metabolism, inhibiting insulin resistance(IR), and anti-atherosclerosis, has attracted widespread attention. In this paper, we summarize recent studies which have contributed to a better understanding of the extent to which adiponectin influences the risks of developing dementia as well as its pathophysiological progression. In addition, some controversial results interlinked with its effects on cognitive dysfunction diseases will be critically discussed.Ultimately we aim to gain a novel insight into the pleiotropic effects of APN levels in circulation and suggest potential therapeutic target and future research strategies.